The Influence of Service Quality and Employee Loyalty on Consumer Purchzase Interest at Cafe Natural on Jalan Adam Malik Gg. Taruna 45 - Fahreza, Tengku Aldi; Ritonga, Nurhabibah; Sipayung, Iskandar Muda (Law and Economics, 2025)
Background This research is motivated by the decline in Cafe Natural's income every year. The purpose of this study is to determine the effect of service quality and employee loyalty on purchasing decisions through purchase interest as an intervening variable at Cafe Natural. The population is all Cafe Natural consumers domiciled in Rantauprapat, while the sample used in this study is 100 Cafe Natural consumers using accidental and purposive sampling techniques. This study uses an explanatory research type. 2) Mehod The analysis method used is a significance test (t-test) and a two-stage regression analysis test using SPSS 23 software.  3) Result and Discussion The results of the study indicate that service quality has a positive effect on purchasing interest, employee loyalty has a positive effect on purchasing interest, and purchasing interest has a positive effect on purchasing decisions. The intervening variable shows that there is a positive effect of the service quality variable on purchasing decisions through purchase interest and there is a positive effect of the employee loyalty variable on purchasing decisions through purchase interest. Based on the results of the study, it is recommended that Cafe Natural conduct research and development, conduct briefings and create SOPs, and improve quality control on product taste. Improve service quality and employee loyalty to suit consumer desires